Application of Problem-Based Learning in Biotechnology Learning Contains Local Potential Jruek Drien Aceh to Improve Problem-Solving and Self-Directed Learning Skills of High School Students - Retcia Aisa; Kusnadi Kusnadi; Rini Solihat (Postgraduate, University of Mataram, 2023)
Mastery of 21st-century skills by students is very dependent on the education and learning process. This research aims to measure the increase in students' problem-solving and self-directed learning skills. One of the biotechnology lessons that highlights the local potential of Aceh's Jrek Drien which can be a solution to overcome this problem. The research method used was quasi-experimental with a nonequivalent control group design. The population in this study was class X (Ten) students with a research sample of two classes, experimental and control classes, the research sample was determined based on convenience sampling. Data collection instruments used a problem-solving skills description test and a self-rating scale self-directed learning (SRSSDL) questionnaire. The results of the research showed that students' problem-solving skills increased with an average gain score for the experimental group of 22.44, while for the control group, it was 15.00 with the N-gain score for the experimental group being in the medium category and the control group being in the medium category of 0.320. Meanwhile, the students' self-directed learning ability obtained an average score of 81.61 for the experimental group and 79.12 for the control group. Students showed a positive response to the implementation of problem-based learning containing the local potential of Jrek Drien in the good category. Based on the research findings and results, it is stated that there is a significant difference in the increase in learning outcomes of students' problem-solving skills and self-directed learning between the experimental and control classes